A new approach of direct recycling of aluminium alloy chips (AA6061) in hot press forging process - Yusuf, Nur Kamilah (2013)
This study introduces a new approach of direct recycling using the hot press forging process that eliminates the two intermediate processes of cold-compact and preheating.